Farmers’ Response Towards Technological Interventions Under Assessment and Refinement - R. K. Singh , S. K. Dubey , R. P. Singh Ratan; D. Das Gupta (Indian Journal of Extension Education, 2013)
Farmers’ responses towards technology assessment and refinment were sutdied in five villages of Karge panchayat of Mandar block in Ranchi District of Jharkhand. Results revealed that all the intervened technologies assessed by the farmers’ were agro-climatically more suitable, more profitable and more compatible, which contributed to their overall appropriateness in comparison to the corresponding farmers’ practices. Overall reaction of the respondents on intervened technologies was found to be positive in terms of selected attributes i.e. socio-cultural compatibility, compatibility with existing farming system components, divisibility of technology, simplicity, compatibility with internal resources of the households, element of risk involved and visibility except their easy availability in the local markets. Majority of the farmers’ felt difficulties in accepting the recommended technologies as such in respect of most of the intervened technologies and preferred the refined technologies which were suitable in their agro-ecological situation and socioeconomic condition.